PELAKSANAAN STRATEGI PEMBELAJARAN PADA MATA PELAJARAN IPS DI SMPN 97 JAKARTA - Wicaksono, Dimas Bagus; Muchtar, Muhammad (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2018)
The observation aims to investigate the implementation of strategy used by the teacher at SMPN 97 East Jakarta. This observatition held on January until June 2016. The methods used qualitative method with interview and observation techniques. The focus of this observation is a strategy of learning used by teacher at SMPN 97 East Jakarta. The object of this observation is a learning strategy that covers lesson plans, syllabus and RPP, media, methods, and evaluation. Instrument of this observation used the implementation table of learning in classroom, interview teachers and students table, and the researcher themselves. The result of this observation is there are used three types of learning strategy: direct learning strategy, discussions learning strategy, and contextual learning strategies. Syllabus and RPP used mostly adopted from Dinas Pendidikan. The media of learning most commonly used are textbooks and worksheets. Then, for the evaluation carried out orally and write. In addition, the supporting factors in learning IPS most commonly used is the slide power point and the internet networking, while the inhibiting factors that are often found is the lack of interest and motivation of students to learn the lessons IPS.